Analysis of the relationship between replication of the Hokkaido genotype of Puumala orthohantavirus and autophagy - Tamiya, Kazuma; Kobayashi, Shintaro; Yoshii, Kentaro; Kariwa, Hiroaki (Virus research, 2022)
•Autophagy is induced by the Hokkaido genotype of Puumala orthohantavirus.•Autophagy suppresses the replication of Hokkaido genotype of Puumala orthohantavirus.•Lysosomal degradation is related to the expression of the nucleocapsid protein. Hantaviruses are potentially fatal zoonotic pathogens of the family Hantaviridae. No human infection by the Hokkaido genotype of Puumala orthohantavirus (PUUV-Hok) has been reported. However, other PUUV genotypes cause hemorrhagic fever with renal syndrome (HFRS) in humans. Autophagy is a highly conserved lysosomal degradation process in eukaryotic cells that affects the replication of various viruses. In this study, we examined the role of autophagy in PUUV-Hok replication. PUUV-Hok infection induced the expression of LC3-II, an autophagosome marker, and the nucleocapsid protein (NP) of PUUV-Hok was colocalized with punctate structures of LC3. Inhibition of autophagy using an siRNA for Atg5, an autophagy-related gene, increased the replication of PUUV-Hok, whereas an autophagy inducer decreased its replication. Inhibition of lysosomal degradation increased the expression of NP and LC3-II. In summary, autophagy was induced by PUUV-Hok infection, which inhibited PUUV-Hok replication in a manner related to the degradation of the NP in lysosomes.